An agent-based framework for building mobile applications - Harroud, Hamid (University of Ottawa (Canada), 2006)
Recent advances in portable computing devices and wireless technology make it possible to provide seamless and ubiquitous services for mobile users. As users move from one location to another, there is a greater need to automatically provide office-like environments that normally have to be configured and setup on an individual basis by each user at each visited location. Due to occasional disconnections, device capabilities and network heterogeneity, users' mobility places a considerable burden on applications to be used by mobile users. On the other hand, it receives little assistance from existing infrastructure and Internet protocols for tracing users' movement and adapting services to satisfy unique characteristics of mobility. This thesis recognizes the importance of managing users' mobility at different levels. From the network level by monitoring network devices and access points to the organizational level by assigning a personalised profile and a specific role to mobile users at visited locations. We propose a set of policy-based agents composing a framework that assists applications and services in dealing with mobility challenges and capable of providing a mobile working environment, similar to the home or office environment, to be used by users wherever they travel and whichever devices they use. The framework enables application designers to more easily build complex mobile and context aware applications. It also provides some basic services so that it can help mobile users simply by making use of the existing support and built in policy-based software agents. In addition, three different applications built upon the framework along with various scenarios have been discussed. Various scenarios illustrate how the framework can be helpful in providing support and services to mobile users. The framework is also a test-bed platform that can be used for the ongoing and future research projects that make use of mobility and context-awareness in MMARL laboratory.
Keywords: Computer Science.